2016
DOI: 10.1136/emermed-2015-205096
|View full text |Cite
|
Sign up to set email alerts
|

Ionised calcium levels in major trauma patients who received blood in the Emergency Department

Abstract: Trauma patients that have sustained blood loss are at risk of hypocalcaemia. Ionised calcium levels fall significantly further even after receiving a small amount of blood product. Prompt recognition and early targeted treatment is needed from arrival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…This compares favourably with the study by Webster et al ,7 who provided evidence of a similar mean calcium level following transfusion in the ED (mean 0.95 mmol/L).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This compares favourably with the study by Webster et al ,7 who provided evidence of a similar mean calcium level following transfusion in the ED (mean 0.95 mmol/L).…”
Section: Discussionsupporting
confidence: 85%
“…This supports the findings of previous in-hospital studies that have demonstrated that blood product administration reduces calcium levels 6 7. These studies disagree on the cut-off point with Giancarelli et al advocating that over 5 units of blood is needed to produce a clinically relevant reduction,6 while others argue that even 1 unit of blood reduces calcium levels below the accepted normal value, consistent with our findings 7…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, current massive transfusion protocols dictate transfusion of high ratios of FFP [29] which has also been independently associated with hypocalcaemia [10, 30,31]. We therefore hypothesize that patients with admission ionized hypocalcaemia as observed in this study are likely to become more severely hypocalcaemic during haemostatic resuscitation [25,26].…”
Section: Discussionmentioning
confidence: 82%
“…Hypocalcaemia was associated with early death mirroring the pattern of death observed in the setting of acute traumatic coagulopathy [23,24]. Early resuscitative measures involving blood transfusion are also likely to further exacerbate hypocalcaemia [25,26].…”
Section: Discussionmentioning
confidence: 88%
“…This could be related to the knowledge that while calcium is an important cofactor to several physiological components of haemostasis, hypocalcemia in acute bleeding is common, and treatment with ABT may worsen this with chelation by citrate additive. 70 It remains that calcium supplementation an important principle of bleeding management with a grade 1B recommendation " calcium should be administered during massive transfusion if calcium concentration is low, to preserve normocalaemia (>0.9 mmol/l)". 14…”
Section: Various Guidelines Including the Society Of Thoracic Surgeonmentioning
confidence: 99%